2003
DOI: 10.1016/s1053-8119(03)00341-0
|View full text |Cite
|
Sign up to set email alerts
|

Attentional modulation of oscillatory activity in human visual cortex

Abstract: The effects of attentional modulation on activity within the human visual cortex were investigated using magnetoencephalography. Chromatic sinusoidal stimuli were used to evoke activity from the occipital cortex, with attention directed either toward or away from the stimulus using a bar-orientation judgment task. For five observers, global magnetic field power was plotted as a function of time from stimulus onset. The major peak of each function occurred at about 120 ms latency and was well modeled by a curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
115
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 61 publications
15
115
2
1
Order By: Relevance
“…In further analogy to Sauseng et al (2005), we found ␣ activity to be significantly suppressed relative to the precue period at sites contralateral to the attended visual hemifield, but did not find any significant increase in the level of oscillatory ␣ activity contralateral to unattended space. This contrasts with previous reports of sustained focal ␣ increases at parieto-occipital sites contralateral to the to-be-ignored position (Worden et al, 2000;Yamagishi et al, 2003;Kelly et al, 2006). However, although divergent, ␣ increases and decreases are not mutually exclusive and might become expressed to different degrees depending on task demand, as suggested previously (Kelly et al, 2006).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In further analogy to Sauseng et al (2005), we found ␣ activity to be significantly suppressed relative to the precue period at sites contralateral to the attended visual hemifield, but did not find any significant increase in the level of oscillatory ␣ activity contralateral to unattended space. This contrasts with previous reports of sustained focal ␣ increases at parieto-occipital sites contralateral to the to-be-ignored position (Worden et al, 2000;Yamagishi et al, 2003;Kelly et al, 2006). However, although divergent, ␣ increases and decreases are not mutually exclusive and might become expressed to different degrees depending on task demand, as suggested previously (Kelly et al, 2006).…”
Section: Discussioncontrasting
confidence: 96%
“…In the case of visuospatial attention deployment, decreases of ␣-activity have been observed contralateral to the attended location (Sauseng et al, 2005), interpreted to reflect enhanced cortical excitability to facilitate future visual processing at the attended position. In addition, ␣ increases have been documented contralateral to the unattended location (Worden et al, 2000;Yamagishi et al, 2003;Kelly et al, 2006), potentially reflecting an active "inhibitory" process protecting against visual input from task-irrelevant positions. Based on these results, it may be suggested that the direction of visuospatial attention is determined by two divergent processes that are reflected in differential changes of ␣ activity over the two hemispheres (facilitatory ␣ decrease and inhibitory ␣ increase over areas tuned to the attended vs unattended hemifields).…”
Section: Introductionmentioning
confidence: 99%
“…For a 10 Hz wavelet, the time-domain SD ( t ) is 87.5 ms, and the time-domain envelope half-width at half-height is 103 ms (cf. Yamagishi et al, 2003). For the broadband filter, the half-width at half-height is 10.4 ms.…”
Section: Methodsmentioning
confidence: 99%
“…A recent MEG study showed that the amplitude of early (ϳ0 -200 ms after stimulus onset) ␣ oscillations in the visual cortex is larger for the attended than for the unattended stimuli (Yamagishi et al, 2003). In addition, stimulus-and nonstimulus-locked ␣-band oscillations are stronger during short-term memory retention than during baseline in intracranial (Halgren et al, 2002) and MEG (Jensen et al, 2002) recordings.…”
Section: ␣-Frequency-band Oscillationsmentioning
confidence: 99%
“…The use of simultaneous EEG and BOLD MRI recordings largely eliminated confounding factors such as attentional shifts that would be evident for separate EEG and neuroimaging sessions (11,(22)(23)(24)(25)(26)(27)(28). In more detail, the present study not only included comparisons of motion stimuli with stationary dot patterns of equal overall luminance and contrast, but also differential paradigms contrasting motion stimuli against each other.…”
Section: Introductionmentioning
confidence: 99%